INTERNETUL, CA „MOTOR AL SCHIMBĂRILOR”, ÎN VIZORUL CERCETĂRII ȘTIINȚIFICE - Moraru, Victor; Pintilii, Ionel (My University, 2022)
The astonishing rise of information technology over the past decades and the spectacular rise of the Internet have generated a veritable avalanche of academic studies. The purpose of the article is to present an overview of the investigations dedicated to the Internet phenomenon. Developing the acceptance of the Internet as an ”engine of change”, the researchers show many aspects of the massive changes produced by the evolution of the Internet (sociology of the Internet, the influence of the Internet on the development of society, the new economy, the cybersphere opportunities, cultural, social and political aspects of the Internet). The article refers to several relevant studies in the field, examines the main directions of academic research related to computer-mediated communication, highlights the contribution in clarifying the particularities of the phenomenon that belongs to various authors, reveals how the characteristics and social impact of the Internet were analyzed and argued.
THe internet, as an ”engine of change”, in the view of scientific research
Keywords: global communication; information society; information technologies; social impact of the Internet; comunicare globală; societatea informațională; tehnologii informaționale; impactul social al Internetului